Sustained Receptor Activation and Hyperproliferation in Response to Granulocyte Colony-stimulating Factor (G-CSF) in Mice with a Severe Congenital Neutropenia/Acute Myeloid Leukemia–derived Mutation in the G-CSF Receptor Gene - Hermans, Mirjam H.A. (The Rockefeller University Press, 1999)
In approximately 20% of cases of severe congenital neutropenia (SCN), mutations are found in the gene encoding the granulocyte colony-stimulating factor receptor (G-CSF–R). These mutations introduce premature stop codons, which result in truncation of 82–98 COOH-terminal amino acids of the receptor. SCN patients who develop secondary myelodysplastic syndrome and acute myeloid leukemia almost invariably acquired a GCSFR mutation, suggesting that this genetic alteration represents a key step in leukemogenesis. Here we show that an equivalent mutation targeted in mice (gcsfr-Δ715) results in the selective expansion of the G-CSF– responsive progenitor (G-CFC) compartment in the bone marrow. In addition, in vivo treatment of gcsfr-Δ715 mice with G-CSF results in increased production of neutrophils leading to a sustained neutrophilia. This hyperproliferative response to G-CSF is accompanied by prolonged activation of signal transducer and activator of transcription (STAT) complexes and extended cell surface expression of mutant receptors due to defective internalization. In view of the continuous G-CSF treatment of SCN patients, these data provide insight into why progenitor cells expressing truncated receptors clonally expand in vivo, and why these cells may be targets for additional genetic events leading to leukemia.